2007
DOI: 10.1096/fj.06-7153com
|View full text |Cite
|
Sign up to set email alerts
|

Physical manipulation of calcium oscillations facilitates osteodifferentiation of human mesenchymal stem cells

Abstract: The role of cytosolic calcium oscillation has long been recognized in the regulation of cellular and molecular interactions. Information embedded in calcium oscillation can provide molecular cues for cell behavior such as cell differentiation. Although calcium dynamics are versatile and likely to depend on the cell type, the calcium dynamics in human mesenchymal stem cells (hMSCs) and its role in differentiation are yet to be fully elucidated. In the present study we characterized the calcium oscillation profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 44 publications
11
166
1
Order By: Relevance
“…[1][2][3] Within cells and tissues, ionic currents and electric potentials exist naturally and influence cell and tissue function and development. 1,4 Disruption or alteration of ionic gradients or cell surface charges by an applied electric field can lead to changes in cell signaling pathways and gene expression, resulting in differences in differentiation, proliferation, and mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Within cells and tissues, ionic currents and electric potentials exist naturally and influence cell and tissue function and development. 1,4 Disruption or alteration of ionic gradients or cell surface charges by an applied electric field can lead to changes in cell signaling pathways and gene expression, resulting in differences in differentiation, proliferation, and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Disruption or alteration of ionic gradients or cell surface charges by an applied electric field can lead to changes in cell signaling pathways and gene expression, resulting in differences in differentiation, proliferation, and mobility. [3][4][5] Since the discovery of the natural electrical properties of bone, the idea of coupling endogenous and exogenous electrical activity has been introduced as a possible tool to promote bone fracture healing and differentiation of osteoprogenitor cells. [6][7][8][9][10] Mechanical and electrical stimuli have been known for some time to affect the properties and regenerative capacity of skeletal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold of the progenitor cells like MSCs makes it unique in understanding the Ca 2+ homeostasis, for example, human MSCs (hMSCs) exhibit spontaneous Ca 2+ oscillations, a phenomenon not routine in other matured cells and progenitors with a few exceptions [32] though like other cell types in MSCs Ca 2+ oscillations are triggered by influx of extracellular Ca 2+ and release from endoplasmic reticulum (ER) via inositol 1,4,5-trisphosphate receptors (IP3Rs) and ryanodine receptors by calciuminduced calcium release [27]. There are studies that suggest mesenchymal stem cells respond to the extracellular Ca 2+ levels sensed by calcium sensing receptor (CaSR) in the cell membrane for its proliferation and differentiation [33].…”
Section: Mesenchymal Stem Cells React Differently To Stress Pathologymentioning
confidence: 99%
“…Other studies evaluated the optimal conditions for the differentiation of MSCs to tenocytes, chondrocytes, or bone cells The results showed that mesenchymatous cell differentiation toward a tendon or bone phenotype depended on the degree of tensile loading: higher tensile loads promoted osteogenic differentiation (38). Mechanosensitive calcium permeable channels, such as the TRP channel, generate changes in intracellular calcium concentration in response to various mechanical stimuli (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Activation of these channels at the level of plasma membrane of MSCs would induce intracellular calcium release and confirm the hypothesis that the mechanical tension could also activate MSCs in the pathological process that leads to the development of the SpAs (55-57).…”
Section: Immunoregulationmentioning
confidence: 99%